2012
DOI: 10.1002/asi.22667
|View full text |Cite
|
Sign up to set email alerts
|

Patient decision‐making modes and causes: A preliminary investigation

Abstract: A recent study of patient decision making regarding acceptance of an implantable cardiac defibrillator (ICD) provides a substantial but nonrandom sample (N = 191) of telephone interviews with persons who have made an affirmative decision regarding an ICD. Using a coding scheme developed through qualitative analysis of transcribed interviews, these data can be subjected to exploratory statistical analysis. The reasons given by respondents for getting the ICD differed by both region and gender, and show some cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Central to this process of adjusting and accepting was finding ways to manage the ICD, while moving forward with activities of everyday life. Similar to findings in other studies (Kantor, Bullinger, & Gal, 2012;Morken et al, 2010;Zeigler & Nelms, 2009), the ICD was described as providing participants with a newfound sense of safety that did not exist prior to its implantation. The ICD shifted from being something that symbolized an increase in at-risk status to a technology that prevented them from being at risk.…”
Section: Discussionsupporting
confidence: 64%
“…Central to this process of adjusting and accepting was finding ways to manage the ICD, while moving forward with activities of everyday life. Similar to findings in other studies (Kantor, Bullinger, & Gal, 2012;Morken et al, 2010;Zeigler & Nelms, 2009), the ICD was described as providing participants with a newfound sense of safety that did not exist prior to its implantation. The ICD shifted from being something that symbolized an increase in at-risk status to a technology that prevented them from being at risk.…”
Section: Discussionsupporting
confidence: 64%
“…This demonstrates the need to develop tools that provide patients with health information that is easy to access and that is recognizably of quality. Despite the increases in patients accessing health information online, little research has been done to demonstrate why consumers trust specific digital sources (Kantor, Bullinger, & Gal, 2012), and patients still cite the need to determine the quality of a source (McKemmish et al, 2009). Perceived ease of access and quality are factors affecting use rates of healthcare technological tools (Rogers, 1995;Silvestre, Sue, & Allen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Gender: despite little mention of potential gender differences, one study found that women were 2.7 times more likely than men to actively confirm their ICD decision to others and consider the physician to be a detailed information giver rather than authority figure. 55,66 Passivity was influenced by the degree of importance assigned to various situational factors:…”
Section: Cluster 2: the Process Of Decision-makingmentioning
confidence: 99%